INCREASING INCOME OF CHICKEN FARMERS THROUGH TRAINING ON THE USE OF SIDE PRODUCTS OF LAYERING CHICKENS IN NORTH KONAWE DISTRICT - Putera, Asrip; Sinarwaty, Sinarwaty; Rostin, Rostin; Balaka, Muh. Yani; Isalman, Isalman; Asni, Nur; Nawy, Eliza Agustriani (Yayasan Education and Social Center, 2023)
The laying hen farming business is one of the businesses that has great potential to be developed in North Konawe Regency, considering that the need for eggs from the people of North Konawe Regency is quite high. The supply and demand for eggs is sometimes unbalanced where demand is higher, so that to meet the need for eggs, the people of North Konawe Regency have to import from outside the district and province. The growth of the laying hen farming business in North Konawe Regency is a positive thing for the regional economy, but on the other hand, laying hen breeders have relatively not looked at the other side of the laying hen farming business. Farmers only focus on the core business, namely producing as many eggs as possible, so the side products of the laying hen farming business are relatively sidelined. Side products can increase the income of laying hen farmers if managed well, but so far farmers have not realized that there are several products that can become side products from laying hen farms. Several problems related to the problems faced by laying hen farmers in North Konawe Regency, namely; Firstly, knowledge of laying hen breeders regarding the benefits and advantages of side products from livestock businesses is still relatively lacking. Second, the knowledge or ability of laying hen breeders in managing side products from the laying hen farming business is relatively minimal. Third, the marketing of various side products from the laying hen farming business is relatively not well segmented. This activity was carried out in Bendewuta Village, Oheo District, North Konawe Regency with 21 participants attending, consisting of laying hen breeders and the community. The resulting activity achievements are (1). Increased understanding of laying hen breeders about the benefits or advantages of managing Side Products of laying hens. (2). Increasing the knowledge (capacity) understanding of laying hen breeders so that they are able to manage or utilize side products of laying hens. (3). Increasing the ability to market side products from laying hen farming businesses.